Development of Low Cost Electronic Nose - Marni Azira, Markom; Ali Yeon, Md Shakaff; Abdul Hamid, Adom; Nazifah, Ahmad Fikri; Shah Fenner Khan; Abu Hassan, Abdullah; Che Muhammad Nor, Che Isa (Universiti Malaysia Perlis, 2010)
The development of electronic noses have been on the rise due to their apparent benefits as it has been proved to solve many problems which is included food quality control, environmental monitoring and etc. However, the commercial electronic nose always known as an expensive and complicated system in recent market. This paper presents the work of the development of a low cost electronic nose which is developed to be cost efficient as it was made using off-the-shelf components. The electronic nose consists of an array of sensory system which integrated with RCM 4000 microcontroller and artificial neural network as the pattern recognition. The completed electronic nose, then, was tested to discriminate a few essences and the test conducted showed that electronic nose was able to perform a profile for the each essence and can be trained using artificial neural network analysis.